Development of an anti-Pseudomonas aeruginosa therapeutic monoclonal antibody WVDC-5244 - Horspool, Alexander M.; Sen-Kilic, Emel; Malkowski, Aaron C.; Breslow, Scott L.; Mateu-Borras, Margalida; Hudson, Matthew S.; Nunley, Mason A.; Elliott, Sean; Ray, Krishanu; Snyder, Greg A.; Miller, Sarah Jo; Kang, Jason; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The rise of antimicrobial-resistant bacterial infections is a crucial health concern in the 21st century. In particular, antibiotic-resistant Pseudomonas aeruginosa causes difficult-to-treat infections associated with high morbidity and mortality. Unfortunately, the number of effective therapeutic interventions against antimicrobial-resistant P. aeruginosa infections continues to decline. Therefore, discovery and development of alternative treatments are necessary. Here, we present pre-clinical efficacy studies on an anti-P. aeruginosa therapeutic monoclonal antibody. Using hybridoma technology, we generated a monoclonal antibody and characterized its binding to P. aeruginosa in vitro using ELISA and fluorescence correlation spectroscopy. We also characterized its function in vitro and in vivo against P. aeruginosa. The anti-P. aeruginosa antibody (WVDC-5244) bound P. aeruginosa clinical strains of various serotypes in vitro, even in the presence of alginate exopolysaccharide. In addition, WVDC-5244 induced opsonophagocytic killing of P. aeruginosa in vitro in J774.1 murine macrophage, and complement-mediated killing. In a mouse model of acute pneumonia, prophylactic administration of WVDC-5244 resulted in an improvement of clinical disease manifestations and reduction of P. aeruginosa burden in the respiratory tract compared to the control groups. This study provides promising pre-clinical efficacy data on a new monoclonal antibody with therapeutic potential for P. aeruginosa infections.